The Potential of Camellia sinensis Extract to Prevent HIV/AIDS Transmission Risk Through the Inhibition of Syncytium, GP120, and GP41 Formation - Retno Pudji Rahayu (Journal of International Dental and Medical Research, 2019)
Until now, HIV/AIDS is still a public health issue that needs serious attention. Vaccines for HIV currently fare far from expectations. Thus, the development of an effective, safe, and affordable anti-HIV treatment is essential to saving the lives of individuals already infected and at-risk with HIV. One of the natural ingredients that is thought to have a potential as an antiviral is green tea (Camellia sinensis). The largest green tea contents are flavonoids and epigallocatechin gallate (EGCG) that are suspected to have anti-HIV-1 effects by preventing the binding of gp120 and gp41 to T cell CD4 molecules. This study aims to analyze the potential of green tea extract in inhibiting the activity of HIV-1 infection through inhibitions to the formation of Syncytium, gp120, and gp41 and its development as a preclinical therapy based on the content of bioactive compounds contained in green tea extract. The study proves that green tea extract 10mg/ml has the ability to inhibit the formation of Syncytium and inhibit the attachment of gp120 and gp41 HIV virus to CD4 T cells in vitro. Thus, the process of HIV infection and fusion to target cells can be inhibited so that HIV/AIDS transmission can be inhibited. The conclusion is that green tea extracts, containing EGCG components, may be used as herbal-based anti-HIV candidates.